Traditional medicine in Incahuasi: An ethnobotanical study [version 1; peer review: 2 approved, 1 approved with reservations] - María Susana Picón Pérez; Jorge Guillermo Morales Ramos; Carlos Alberto Chirinos Ríos; Sofía Mariagracia Morales Ramírez; Enrique Guillermo Llontop Ynga; Luis A. Coaguila Cusicanqui; Darwin A. León-Figueroa; Marco Agustín Arbulú Ballesteros (F1000Research, 2023)
Introduction: Understanding the use of medicinal plants as herbal medicines is considered essential for the survival and continuity of humanity. Since ancient times, the origin and development of natural and traditional medicine have been intrinsically linked to humanity struggle for survival. Nowadays, ethnobotanical studies are employed as a tool for the preservation and conservation not only of taxonomic biodiversity but also of cultural biodiversity. Methodology: A descriptive research with a quantitative, non-experimental cross-sectional design was carried out. The study was conducted in six Quechua-speaking communities in the district of Incahuasi (3,000 meters above sea level), selected for convenience considering factors such as altitude, accessibility, and proximity to the city. A questionnaire was administered to 32 residents from the communities, who shared their knowledge about medicinal plants, providing relevant information about them. The gender of the participants was considered because men and women use traditional medicine and the knowledge of them is transmitted from parents to children. Results: During the study, a total of 46 medicinal species were recorded, belonging to 42 genera and 22 botanical families. The most representative medicinal families used by the informants of the communities were Asteraceae (30.4%) and Lamiaceae (15.2%). It is also worth mentioning the genera Salvia and Baccharis, with 3 and 2 species respectively, which are commonly used to treat various ailments and diseases. Conclusions: Ethnobotanical information was collected on the medicinal plants used by the community members of the selected communities in Incahuasi, and the corresponding data were recorded. A total of 46 plants were collected, with the majority belonging to the Asteraceae and Lamiaceae families.